2005
DOI: 10.1038/sj.sc.3101801
|View full text |Cite
|
Sign up to set email alerts
|

Subacute delayed ascending myelopathy after low spine injury: case report and evidence of a vascular mechanism

Abstract: Study design: Case report of a patient with subacute delayed myelopathy after an acute low thoracic spine injury. Objectives: To draw awareness to a rarely described complication with potential to add devastating neurological insult to the original spinal cord injury, and to discuss evidence supporting a vascular mechanism. Setting: Health Science Centre, Winnipeg, Manitoba, Canada. Case report: A 35-year-old woman developed clinical and MRI evidence of ascending myelopathy, extending up to C5, 16 days after a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(76 citation statements)
references
References 18 publications
(22 reference statements)
1
75
0
Order By: Relevance
“…Certainly, the central grey matter of the spinal cord is considered the most sensitive to changes in vascular supply. Although limited to a few cases, in both spinal angiography 4 and post-mortem studies, 6 no evidence of arterial or venous occlusion was found. Furthermore, the clinical and radiological pattern of recovery seen in surviving patients argues strongly against an irreversible vascular injury.…”
Section: Possible Aetiologymentioning
confidence: 99%
See 1 more Smart Citation
“…Certainly, the central grey matter of the spinal cord is considered the most sensitive to changes in vascular supply. Although limited to a few cases, in both spinal angiography 4 and post-mortem studies, 6 no evidence of arterial or venous occlusion was found. Furthermore, the clinical and radiological pattern of recovery seen in surviving patients argues strongly against an irreversible vascular injury.…”
Section: Possible Aetiologymentioning
confidence: 99%
“…Ascending cord injury involving at least four segments in the early period following spinal cord injury was first described by Frankel in 1968. Subacute progressive ascending myelopathy (SPAM) represents a rare, poorly understood neurological complication of spinal cord injury [3][4][5][6][7][8] and may develop following an insult to any part of the spinal cord. 4 Patients typically present with an ascending neurological deficit within 3 weeks of the initial spinal cord insult.…”
Section: Introductionmentioning
confidence: 99%
“…The aetiology of this condition is debated but is likely to be due to altered CSF flow secondary to dural adhesions although ischaemic and inflammatory processes have been proposed. 30,31 Imaging reveals a characteristic progression of oedema within the cord which extends more than four segments above the original injury and then typically subsides, but remains above the initial level (Figure 11). The signal abnormality is characteristically central with sparing of the cord periphery.…”
Section: Cord Oedemamentioning
confidence: 99%
“…Any factor exacerbating spinal venous hypertension and/or arterial hypotension, may lead to reduced cord perfusion and SDAM. 3 However, cord ischaemia may be chronic rather than large vessel in aetiology because of the progressive deterioration and response to a variety of interventions.…”
Section: Discussionmentioning
confidence: 99%
“…There have been various treatment trials despite the lack of guidelines, with methyprednisolone often administered empirically. There is no consensus on dose or length of treatment 3 or correlation with response. Cord untethering, duroplasty and cordectomy have also been reported to improve outcome.…”
Section: Prognosismentioning
confidence: 99%